Emergent scale symmetry: connecting inflation and dark energy - Rubio, Javier; Wetterich, Christof (Arxiv, 2017)
In a variable gravity scenario containing an ultraviolet and an infrared fixed point quantum scale invariance emerges at both fixed points. We discuss a particular model for the crossover between the fixed points which can naturally account for inflation and dark energy using a single scalar field. In the Einstein-frame formulation the potential can be expressed in terms of Lambert functions, interpolating between a power-law inflationary potential and a mixed quintessence potential. For two natural heating scenarios, the transition between inflation and radiation domination proceeds through a "graceful reheating" stage. The radiation temperature significantly exceeds the temperature of Big Bang Nucleosynthesis.
Gesehen am 13.07.2017